Dynamic queuosine changes in tRNA couple nutrient levels to codon choice in Trypanosoma brucei. Issue 22 (9th December 2021) - Dixit, Sameer; Kessler, Alan C; Henderson, Jeremy; Pan, Xiaobei; Zhao, Ruoxia; D'Almeida, Gabriel Silveira; Kulkarni, Sneha; Rubio, Mary Anne T; Hegedűsová, Eva; Ross, Robert L; Limbach, Patrick A; Green, Brian D; et al.
Abstract: Every type of nucleic acid in cells undergoes programmed chemical post-transcriptional modification. Generally, modification enzymes use substrates derived from intracellular metabolism, one exception is queuine (q)/queuosine (Q), which eukaryotes obtain from their environment; made by bacteria and ultimately taken into eukaryotic cells via currently unknown transport systems. Here, we use a combination of molecular, cell biology and biophysical approaches to show that in Trypanosoma brucei tRNA Q levels change dynamically in response to concentration variations of a sub-set of amino acids in the growth media. Most significant were variations in tyrosine, which at low levels lead to increased Q content for all the natural tRNAs substrates of tRNA-guanine transglycosylase (TGT). Such increase results from longer nuclear dwell time aided by retrograde transport following cytoplasmic splicing. In turn high tyrosine levels lead to rapid decrease in Q content. Importantly, the dynamic changes in Q content of tRNAs have negligible effects on global translation or growth rate but, at least, in the case of tRNA Tyr it affected codon choice. These observations have implications for the occurrence of other tunable modifications important for 'normal' growth, while connecting the intracellular localization of modification enzymes, metabolites and tRNAs to codon selection and implicitly translational output.